Changes in pain intensity after discontinuation of long-term opioid therapy for chronic noncancer pain. Issue 10 (October 2018) - McPherson, Sterling; Lederhos Smith, Crystal; Dobscha, Steven K.; Morasco, Benjamin J.; Demidenko, Michael I.; Meath, Thomas H.A.; Lovejoy, Travis I.
Abstract : Abstract: Little is known about changes in pain intensity that may occur after discontinuation of long-term opioid therapy (LTOT). The objective of this study was to characterize pain intensity after opioid discontinuation over 12 months. This retrospective U.S. Department of Veterans Affairs (VA) administrative data study identified N = 551 patients nationally who discontinued LTOT. Data over 24 months (12 months before and after discontinuation) were abstracted from VA administrative records. Random-effects regression analyses examined changes in 0 to 10 pain numeric rating scale scores over time, whereas growth mixture models delineated pain trajectory subgroups. Mean estimated pain at the time of opioid discontinuation was 4.9. Changes in pain after discontinuation were characterized by slight but statistically nonsignificant declines in pain intensity over 12 months after discontinuation (B = −0.20, P = 0.14). Follow-up growth mixture models identified 4 pain trajectory classes characterized by the following postdiscontinuation pain levels: no pain (average pain at discontinuation = 0.37), mild clinically significant pain (average pain = 3.90), moderate clinically significant pain (average pain = 6.33), and severe clinically significant pain (average pain = 8.23). Similar to the overall sample, pain trajectories in each of the 4 classes were characterized by slight reductions in pain over time, with patients in the mild and moderate pain trajectory categories experiencing the greatest pain reductions after discontinuation (B = −0.11, P = 0.05 and B = −0.11, P = 0.04, respectively). Pain intensity after discontinuation of LTOT does not, on average, worsen for patients and may slightly improve, particularly for patients with mild-to-moderate pain at the time of discontinuation. Clinicians should consider these findings when discussing risks of opioid therapy and potential benefits of opioid taper with patients. Abstract : Supplemental Digital Content is Available in the Text.Pain intensity as assessed by numeric rating scale pain intensity scores did not significantly change in the 12 months after discontinuation of long-term opioid therapy.